AUDIT KEPATUHAN SOP WORK ORDER TESTING PADA PT XYZ - Natalia Ivana Bella Tampubolon; Sugeng Riadi (ABEC Indonesia, 2021)
This study report discusses the importance of implementing a standard operating procedure (SOP) for work order testing in carrying out material testing. The purpose of this study was to audit the level of employee compliance with the SOP in carrying out material testing based on the work order testing SOP. This study uses data that has been analyzed using descriptive methods. The results of the study stated that the SOP compliance audit for work order testing was declared compliant with a percentage of 91.3%. However, there were several findings, namely the delivery of material testing samples and the material testing process was not carried out on time according to the predetermined schedule.